Exploring program management competences for various program types. Issue 3 (April 2016) - Miterev, Maxim; Engwall, Mats; Jerbrant, Anna
Abstract: This paper challenges the implicit 'one-size-fits-all' assumption that dominates mainstream program management competence literature. Findings from case studies of 10 programs executed in a large pharmaceutical company suggest that different programs require different competences of program managers. Based on the Pellegrinelli's (1997) program typology we put forward a framework, linking specific management competences to program types. By establishing the link between the program typologies literature and program management competence literature, the paper shows that programs should not be treated as a generic and homogenous category in discussions on program management competences. In addition, the findings highlight program content as a significant contingency variable for understanding program management dynamics. The paper suggests a conceptual framework that combines program types with program management competence profiles that could be applied to appointment decisions, staff assessments and organizational development. Highlights: Questions 'one-size-fits-all' assumption in program management competence research Explores program management competences required to manage 10 different programs Shows how different program types require different sets of competences Identifies three ideal profiles—the Coordinator, the Commander, and the Convincer Highlights the importance of program content as a contingency dimension